2015
DOI: 10.1016/j.polymer.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Modification of linear prepolymers to tailor heterogeneous network formation through photo-initiated polymerization-induced phase separation

Abstract: Polymerization-induced phase separation (PIPS) was studied in ambient photopolymerizations of triethylene glycol dimethacrylate (TEGDMA) modified by poly(methyl methacrylate) (PMMA). The molecular weight of PMMA and the rate of network formation (through incident UV-irradiation) were varied to influence both the promotion of phase separation through increases in overall free energy, as well as the extent to which phase development occurs during polymerization through diffusion prior to network gelation. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 41 publications
(61 reference statements)
0
33
0
Order By: Relevance
“…In addition to comonomers, each formulation also included a varying amount (based on wt%) of a nonreactive, thermoplastic, fluoropolymer: poly(vinyl diene) fluoride (PVDF). Previous studies of phase‐separating polymerizations have often turned toward the use of a nonreactive additive to increase overall free energy of a polymerizing resin and thus promote the formation of heterogeneous structure through diffusion of incompatible phases . Here, PVDF is chosen as the nonreactive additive due to the favorable properties it imparts on the resulting coating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to comonomers, each formulation also included a varying amount (based on wt%) of a nonreactive, thermoplastic, fluoropolymer: poly(vinyl diene) fluoride (PVDF). Previous studies of phase‐separating polymerizations have often turned toward the use of a nonreactive additive to increase overall free energy of a polymerizing resin and thus promote the formation of heterogeneous structure through diffusion of incompatible phases . Here, PVDF is chosen as the nonreactive additive due to the favorable properties it imparts on the resulting coating.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of phase-separating polymerizations have often turned toward the use of a nonreactive additive to increase overall free energy of a polymerizing resin and thus promote the formation of heterogeneous structure through diffusion of incompatible phases. [13,[25][26][27][28] Here, PVDF is chosen as the nonreactive additive due to the favorable properties it imparts on the resulting coating. This includes resistance to solvents, mechanical strength, and rigidity, as well as low surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…Szczepanski et al [ 30 ] investigated the photo-polymerization of triethylene glycoldimethacrylate (TEGDMA) modified by poly(methyl methacrylate) (PMMA), which induced the phase separation and formed the heterogeneous network. The obtained tan delta profile showed the formation of two separated phases, one rich in TEGDMA, and the other rich in TEGDMA/PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important concerns about incorporating nonreactive inorganic moiety into a photopolymerizing formulation is their tendency to undergo polymerization‐induced phase separation (PIPS). [1b,3] The Gibbs free energy of mixing thermodynamically determines the advancement of phase separation in a multicomponent mixture ΔGmix = ΔHmix TΔSmix…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the molecular weight of the nonreactive part not only promotes PIPS but also changes the mechanism of phase separation. Samples with a high molecular weight nonreactive part undergo phase separation through spinodal decomposition while samples with low molecular weight polymer additives undergo phase separation through nucleation and growth . Other studies have revealed that miscibility and crosslink density can affect the final morphology.…”
Section: Introductionmentioning
confidence: 99%